2014
DOI: 10.3390/molecules19011047
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and Nutritional Quality of the Goat Meat by-Product “Sarapatel”

Abstract: Abstract:Goat "sarapatel" is a product made from blood and viscera. For the first time, the microbiological and nutritional quality of "sarapatel" samples (n = 48) sold under different conditions (in street markets, butcher shops, and supermarkets under refrigeration, frozen or at room temperature) was evaluated. Goat "sarapatel" is a nutritive food, with each 100 g providing, on average, 72 g of moisture, 2 g of ash, 18 g of protein, 9 g of lipids, 2 g of carbohydrates, 282 mg of cholesterol, and high amounts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 30 publications
(39 reference statements)
3
25
0
Order By: Relevance
“…In contrast to reduction of C18:3 n-3 of the PUFA identified in Altay sheep fat, no changes was found in C18:2 n-9 after storage for 50 days. Considering the decrease of PUFA, the percentage of C18:2 n-9 kept relatively stable, which is in agreement with the results by Brasil, L. and Zhang, H. et al 25,27 . No obviously changes in goat and beef fat.…”
Section: The Changes Of Fatty Acids In Altay Sheep Fatsupporting
confidence: 81%
See 1 more Smart Citation
“…In contrast to reduction of C18:3 n-3 of the PUFA identified in Altay sheep fat, no changes was found in C18:2 n-9 after storage for 50 days. Considering the decrease of PUFA, the percentage of C18:2 n-9 kept relatively stable, which is in agreement with the results by Brasil, L. and Zhang, H. et al 25,27 . No obviously changes in goat and beef fat.…”
Section: The Changes Of Fatty Acids In Altay Sheep Fatsupporting
confidence: 81%
“…Ref. 25 reported that the palmitic acid C16:0 and stearic acid C18:0 are the most abundant SFA in sheep meat and the oleic acid C18:1 n-9 in sheep meat as dominant MUFA followed by palmitoleic acid C16:1 . A small quantity of C18:3 n-3 was also found in goat meat reported by Santercole, V. et al 26 .…”
Section: Changes Of the Fatty Acid Contentmentioning
confidence: 99%
“…However, at frozen temperatures of −12, −18 and −24 • C, liver meat shelf life could be extended to 4, 12 and 18 months, respectively [50]. These preservative mechanisms are employed to ensure that EBPs are safe for consumption by the end-users, although some authors have reported the presence of different microorganisms such as Escherichia coli, Staphylococcus aureus, Clostridium perfringens in EBPs from cattle, pig and sheep [51][52][53]. Moreover, this has been attributed to poor hygienic quality of the products due to their uncontrolled processing, storage, and handling.…”
Section: Effect Of Thermal Processing and Preservation Methods On Quamentioning
confidence: 99%
“…The livestock industry may increase profitability by converting as much edible by-products as possible into food products. The use of by-products would also reduce the cost of waste management and the negative environmental impact (Brasil et al, 2014).…”
Section: Introductionmentioning
confidence: 99%